Monetary Policy and its Implication for Balance of Payment Stability in Nigeria Between 1986-2015 - M.O, Mukolu; A.O, Illugbemi; J.A, Otalu (Asian Journal of Economic Modelling, 2017)
An assessment of the impact of monetary policy on balance of payments in Nigeria from 1986-2015 was investigated. The data used for this study is mainly secondary data and was analyzed using ARDL co integration technique. The results showed the net trade (NT), money supply (M2) and bank credit to private sector (BCP) all have long run effect on the balance of payment while the differenced money supply (DM2), net trade and bank credit all showed the short run relationship with the balance of payment. From the overall analyses done on the variables, it was concluded that all variables exhibited relationships both in the long and short run respectively i.e are jointly significant. It’s therefore recommended that government through the monetary authority should ensure that the domestic money stock is consistent with macroeconomic objectives, put adequate policies in place that will stabilize money circulation in order to avoid excess liquidity in the economy which may lead to inflation. Export diversification and non-oil sector exports should be encouraged as this will enhance BOP position in Nigeria.